GEDUNG PAMERAN PRODUK ARSITEKTUR DAN INERIOR DI KOTA MAKASSAR DENGAN PENDEKATAN ECO-OFFICE - Husnul, Muhammad; Rahayu, Irma; Burhanuddin, Burhanuddin (Nature : National Academic Journal of Architecture, 2014)
Plaining and design of the bulding aims to design building of architecture and interior products exhibitions in the city of Makassar with emphasis Eco-Office, this design is limited to a few problems, there are the architectural issue, particulary spatial, space recurements and building appearance. The method issued is the study of literature/ literary studies, surveys (in the from of field observations and data collection of function of the building where has a similar to the trade fair), and analsis of the data obtained. The result of the creation of the design architecture and interior products exhibition builing in the city of Makassar with emphaisis Eco-Office, with the ability of building to accommodate currently building development without compromising environmental aspects.